United Kingdom Time Use Survey, 2014-2015 - Gershuny, J (University of Oxford, 2017)
The United Kingdom Time Use Survey, 2014-2015 (UKTUS) is a large-scale household survey that provides data on how people aged 8 years and over in the UK spend their time. At the heart of the survey is a time diary instrument in which respondents record their daily activities. Time diaries record events sequences for prescribed periods, usually a single day. They are an effective means of capturing rich data on how people spend their time, their location throughout the day, and who they spend their time with. The sample was based on households, and household members eight years and over completed time-diaries for one weekday and one weekend day. In addition, those in paid work were asked to complete a weekly work schedule. All individuals who completed a time diary were invited to take part in an interview, and someone in the household was selected to take part in a household interview. These interviews provide additional demographic, economic, and social information about households and individuals.